2008
DOI: 10.1074/jbc.m708291200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the Photosystem II Subunit PsbS and Xanthophylls Studied in Vivo and in Vitro

Abstract: The photosystem II subunit PsbS is essential for excess energy dissipation (qE); however, both lutein and zeaxanthin are needed for its full activation. Based on previous work, two models can be proposed in which PsbS is either 1) the gene product where the quenching activity is located or 2) a proton-sensing trigger that activates the quencher molecules. The first hypothesis requires xanthophyll binding to two PsbS-binding sites, each activated by the protonation of a dicyclohexylcarbodiimide-binding lumen-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
101
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 72 publications
5
101
0
3
Order By: Relevance
“…This genotype lacks both CP26 and CP24, the two most effective Lhc proteins in Viola>Zea exchange (Morosinotto et al, 2003) and has reduced CP29. Since Zea has been shown to decrease the activation energy required for the transition from unquenched to quenched conformation , we interpret these results as the effect of a slower transduction of conformational change signal, upon protonation of PsbS, to Lhc proteins, where quenching is catalyzed even in the absence of Zea bound (Briantais, 1994;Bonente et al, 2007). The high levels of qE in koCP24/26 mutants, although with slower kinetics than the wild type, suggest that the major LHCII, which is still present with only 50% of CP29 proteins, might play a role in qE.…”
Section: The Npq Rise Kinetics Are Affected By Lack Of Zea-exchangingmentioning
confidence: 83%
See 1 more Smart Citation
“…This genotype lacks both CP26 and CP24, the two most effective Lhc proteins in Viola>Zea exchange (Morosinotto et al, 2003) and has reduced CP29. Since Zea has been shown to decrease the activation energy required for the transition from unquenched to quenched conformation , we interpret these results as the effect of a slower transduction of conformational change signal, upon protonation of PsbS, to Lhc proteins, where quenching is catalyzed even in the absence of Zea bound (Briantais, 1994;Bonente et al, 2007). The high levels of qE in koCP24/26 mutants, although with slower kinetics than the wild type, suggest that the major LHCII, which is still present with only 50% of CP29 proteins, might play a role in qE.…”
Section: The Npq Rise Kinetics Are Affected By Lack Of Zea-exchangingmentioning
confidence: 83%
“…Besides violaxanthin deepoxidase activation, low lumenal pH exerts control over the thylakoid membrane by reversibly protonating exposed acidic residues, as suggested by the inhibition of NPQ by dicyclohexylcarbodiimide (DCCD), a reagent that modifies acidic residues that undergo reversible protonation (Ruban et al, 1992). Whereas 14 C DCCD binding antenna proteins CP26 and CP29 are located between the inner antenna and the LHCII , Pesaresi et al, 1997, the site of DCCD inhibition of qE is located in PsbS (Li et al, 2004), an Lhc-like protein (Li et al, 2000) that likely does not bind pigments (Sundaresan et al, 1995;Dominici et al, 2002) but exerts its function by interacting with Lhc proteins (Bonente et al, 2007;Teardo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…qE, the fastest quenching component, requires the PSII protein, S subunit of PSII (PSBS; Li et al, 2000), which transduces low lumenal pH signal into a quenching reaction by the reversible protonation of two lumen-exposed Glu residues (Li et al, 2004). Although PSBS is not a pigment binding protein (Dominici et al, 2002;Bonente et al, 2008a), its activity in triggering NPQ is enhanced by zeaxanthin, possibly by binding to LHCb proteins, where quenching occurs (Ruban et al, 1999;Caffarri et al, 2001;Holt et al, 2005;Ahn et al, 2008;Avenson et al, 2008;Betterle et al, 2009;Dall'Osto et al, 2012). In green algae, where PSBS is absent (Bonente et al, 2008b), the triggering of qE requires light-harvesting complex stress-related (LHCSR) (Peers et al, 2009), a chlorophyll binding protein sharing with PSBS the capacity of binding dicyclohexylcarbodiimide and transducing the low lumenal pH into a quenching reaction (Peers et al, 2009;Bonente et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Because no pigment binding has been detected either by biochemical analysis (Bonente et al, 2008a) or in in the recent crystal structure (Fan et al, 2015), it is very likely that PsbS is not the quenching site during NPQ. Therefore, it has been suggested that PsbS promotes a reorganization of the photosynthetic membranes in order to induce the formation of a quenching site in the Lhc antenna system (Bassi and Caffarri, 2000;Betterle et al, 2009;Johnson et al, 2011).…”
mentioning
confidence: 99%
“…So far, three proteins have been shown to have a major role in detecting and transducing the low pH signal: the low pH activated violaxanthin de-epoxidase enzyme (VDE; Arnoux et al, 2009) that catalyses the conversion of the xanthophyll violaxanthin into zeaxanthin, a pigment involved in NPQ and other photoprotection mechanisms (Demmig-Adams, 1990;Havaux and Niyogi, 1999); the pigment-binding LhcSR proteins that belong to the Lhc family and are very likely the active site of quenching after protonation of C-terminal residues (Peers et al, 2009;Bonente et al, 2011;Liguori et al, 2013); and the PsbS protein that is protonated on two luminal Glu residues (Li et al, 2000;Li et al, 2004) and is proposed to subsequently promote the reorganization of the photosynthetic apparatus in order to create quenching sites elsewhere (Bassi and Caffarri, 2000;Bonente et al, 2008a;Johnson et al, 2011). It should be noted that efficient energy quenching also requires the presence of Lhc proteins, but this does not require a specific Lhc isoform (Andersson et al, 2001(Andersson et al, , 2003de Bianchi et al, 2008de Bianchi et al, , 2011.…”
mentioning
confidence: 99%